Cardiovascular Hypertension-Mediated Organ Damage in Hypertensive Urgencies and Hypertensive Outpatients - Vallelonga, Fabrizio; Cesareo, Marco; Menon, Leonardo; Airale, Lorenzo; Leone, Dario; Astarita, Anna; Mingrone, Giulia; Tizzani, Maria; Lupia, Enrico; Veglio, Franco; Milan, Alberto (Frontiers in Cardiovascular Medicine, 2022)
Background The prevalence of hypertension mediated organ damage (HMOD) in patients attending the Emergency Department (ED) with symptomatic blood pressure (BP) rise is unknown, and whether HMOD varies between asymptomatic and symptomatic patients with grade 3 hypertension is unclear. Aim This study aimed to investigate cardiac and vascular HMOD in hypertensive urgencies (HU) and asymptomatic outpatients with grade 1–3 hypertension. Methods Patients attending the ED with a symptomatic BP rise ≥180/110 mmHg were prospectively enrolled (HU group), after the exclusion of acute organ damage. HMOD and BP were assessed after 72 h from ED discharge in an office setting. These patients were matched by age and sex to outpatients with grade 3 hypertension (Grade 3 group), and by age, sex, and 72 h office BP values to outpatients with any grade hypertension (Control group). Results A total of 304 patients were enrolled (76 patients in the HU group, 76 in the Grade 3 group, and 152 in the Control group). Grade 3 patients had increased left ventricular mass (LVMi) compared to patients with HU (106.9 ± 31.5 vs. 96.1 ± 30.7 g/m2, p = 0.035). Severe left ventricular hypertrophy (LVH) was more frequent in grade 3 (21.1 vs. 5.3%, p = 0.004), and pulse wave velocity (PWV) was similar in the two groups. There was no difference in LVMi between ED and Control patients (96.1 ± 30.7 vs. 95.2 ± 26.6 g/m2, p = 0.807). LVH prevalence was similar (43.4 vs. 35.5%, p = 0.209, respectively), but patients with HU had thicker interventricular septum (11.9 ± 2.2 vs. 11.1 ± 2.2 mm, p = 0.007). PWV was similar between these two groups. Patients with HU needed more antihypertensive drugs than Control patients (2 vs. 1, p < 0.001). Conclusions Patients with HU had a better cardiac HMOD profile than outpatients with grade 3 hypertension. Their cardiac and vascular HMOD is more comparable to an outpatient with similar in-office BP, although they need more antihypertensive medications.